Smallholder farming and crop variety choice: Maize variety choice in Zambia - De Groote, Hugo; Gitonga, Zachary; Smale, Melinda; Asare-Marfo, Dorene; Kasuta, Earnest; Birol, Ekin; Sonder, Kai (International Food Policy Research Institute, 2014)
Micronutrient deficiency, especially vitamin A deficiency, is a major problem in developing countries (Aguayo and Baker 2005; Black et al. 2008; Kennedy et al. 2003). Various strategies have been developed to combat vitamin A deficiency, including vitamin A supplementation (in the form of capsules), food fortification, and the promotion of household vegetable gardens. In Zambia, where more than half of preschool children are at risk for vitamin A deficiency (Micronutrient Initiative 2009), biannual capsules are provided to children in combination with vaccinations, and sugar is fortified with retinol, the pure form of vitamin A (Fiedler et al. 2013). Unfortunately, rural households are harder to reach with supplementation, and they do not consume many of the fortified processed foods.